The effects of different surgical positions (semi-sitting and lateral position) on the surgical outcomes of large vestibular schwannoma: study protocol for a randomized controlled trial - Xiaolong Wu; Xu Wang; Gang Song; Mingchu Li; Chengbei Hou; Ge Chen; Hongchuan Guo; Xinru Xiao; Jie Tang; Qingtang Lin; Yuhai Bao; Jiantao Liang (Trials, 2022)
Abstract Background There is an ongoing discussion about the advantages and disadvantages of different surgical positions (semi-sitting and lateral position) for vestibular schwannoma surgery. Each position has its advantages, disadvantages, challenges, and risk profiles. The objectives of this study are to compare the effects of different surgical positions (semi-sitting and lateral position) on the outcomes of large vestibular schwannoma, primarily including effectiveness and safety. Methods In this single-centre, open, randomized controlled trial, we will recruit a total of 116 participants according to the inclusion and exclusion criteria who will be randomized to an experimental group or control group. Patients will undergo operations in semi-sitting and lateral positions. The primary endpoint will be the percentage of gross total resection. The secondary endpoints will include the facial nerve function, hearing preservation, surgical position placement time, time of operation (skin-to-skin surgical time), hospital stay, total hospitalization fee, and complications. The follow-up period will be at least 12 months, during which time patients will be evaluated both clinically and radiologically. Discussion This issue is still debated after 30 years since the first large comparative study was published in 1989, so the study will be useful. Therefore, more high-quality studies are required to compare clinical outcomes, complications, and other factors associated with these two positions. Trial registration Chinese Clinical Trial Registry ChiCTR1900027550 . Registered on 17 November 2019